Chromosomal Imbalances in Patients with Congenital Cardiac Defects: A Meta‐analysis Reveals Novel Potential Critical Regions Involved in Heart Development. (11th April 2014) - Thorsson, Thor; Russell, William W.; El‐Kashlan, Nour; Soemedi, Rachel; Levine, Jonathan; Geisler, Sarah B.; Ackley, Todd; Tomita‐Mitchell, Aoy; Rosenfeld, Jill A.; Töpf, Ana; Tayeh, Marwan; Goodship, Judith; et al.
Abstract Objective Congenital cardiac defects represent the most common group of birth defects, affecting an estimated six per 1000 births. Genetic characterization of patients and families with cardiac defects has identified a number of genes required for heart development. Yet, despite the rapid pace of these advances, mutations affecting known genes still account for only a small fraction of congenital heart defects suggesting that many more genes and developmental mechanisms remain to be identified. Design In this study, we reviewed 1694 described cases of patients with cardiac defects who were determined to have a significant chromosomal imbalance (a deletion or duplication). The cases were collected from publicly available databases (DECIPHER, ISCA, and CHDWiki) and from recent publications. An additional 68 nonredundant cases were included from the University of Michigan. Cases with multiple chromosomal or whole chromosome defects (trisomy 13, 18, 21) were excluded, and cases with overlapping deletions and/or insertions were grouped to identify regions potentially involved in heart development. Results Seventy‐nine chromosomal regions were identified in which 5 or more patients had overlapping imbalances. Regions of overlap were used to determine minimal critical domains most likely to contain genes or regulatory elements involved in heart development. This approach was used to refine the critical regions responsible for cardiac defects associated with chromosomal imbalances involving 1q24.2, 2q31.1, 15q26.3, and 22q11.2. Conclusions The pattern of chromosomal imbalances in patients with congenital cardiac defects suggests that many loci may be involved in normal heart development, some with very strong and direct effects and others with less direct effects. Chromosomal duplication/deletion mapping will provide an important roadmap for genome‐wide sequencing and genetic mapping strategies to identify novel genes critical for heart development.